ADJUVANT DERMATOLOGICAL THERAPY - SBTMO, Sociedade Brasileira de TMO; Silva, Marcia de Matos; Souza, Patricia Karla de (JOURNAL OF BONE MARROW TRANSPLANTATION AND CELLULAR THERAPY, 2021)
THE BRAZILIAN SOCIETY FOR BLOOD AND MARROW TRANSPLANTATION (SBTMO) PRESENTS THE BRAZILIAN GUIDELINES ON HEMATOPOIETIC STEM CELL TRANSPLANTATION